1995
DOI: 10.1111/j.1365-2796.1995.tb00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid intolerance in smokers

Abstract: Healthy, normotriglyceridaemic smokers exhibit an abnormal postprandial lipid metabolism consistent with lipid intolerance. It is suggested that postprandial hyperlipidaemia is a characteristic trait of the insulin resistance syndrome and that the defect in lipid removal is related to the low HDL cholesterol in this syndrome. The insulin resistance syndrome is likely to be an important reason for the increased propensity for cardiovascular disease in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 28 publications
7
52
1
2
Order By: Relevance
“…It has been reported that the daytime blood pressure and average 24 hour blood pressure are higher on smoking days than on nonsmoking days (4). After the same fat load was given to smoking and nonsmoking subjects with normal fasting TG levels, serum TG increased significantly, while HDL-C decreased significantly in the smoking subjects (6). Following a glucose load, the blood glucose level increased significantly after smoking in smoking subjects, and insulin and C-peptide levels also increased significantly, while the blood glucose level increased only Nonobese subjects: body mass index < 25, obese subjects: body mass index ≥ 25 NS: nonsmokers, S: smokers Mean ± SD **: p < 0.02, ***: p < 0.01 The waist circumference of each group of nonobese subjects was significantly smaller than that of each group of obese subjects (p < 0.01).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that the daytime blood pressure and average 24 hour blood pressure are higher on smoking days than on nonsmoking days (4). After the same fat load was given to smoking and nonsmoking subjects with normal fasting TG levels, serum TG increased significantly, while HDL-C decreased significantly in the smoking subjects (6). Following a glucose load, the blood glucose level increased significantly after smoking in smoking subjects, and insulin and C-peptide levels also increased significantly, while the blood glucose level increased only Nonobese subjects: body mass index < 25, obese subjects: body mass index ≥ 25 NS: nonsmokers, S: smokers Mean ± SD **: p < 0.02, ***: p < 0.01 The waist circumference of each group of nonobese subjects was significantly smaller than that of each group of obese subjects (p < 0.01).…”
Section: Discussionmentioning
confidence: 96%
“…Although it has been reported that smoking influences body mass index (BMI) (2) and arteriosclerotic diseases (3), as well as blood pressure (4,5), lipid metabolism (5,6) and glucose metabolism (7,8), it has not been clarified whether there is a difference in the prevalence of hypertension or metabolic disorders between nonobese and obese persons based on the presence or absence of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…A standardized meal test (energy content 900 kcal/3.75 MJ; 51 g of fat) was performed as described before, 15 and glucose, insulin and blood triglyceride levels were followed for 8 h every 2 h. Safety evaluations (reporting of adverse events, physical examination, retinal photography, blood pressure, electrocardiogram, and clinical routine laboratory tests) were performed at regular intervals during the study. Selfmonitored blood glucose measurements (SMBG) were carried out during the titration period in order to avoid hypoglycaemia.…”
Section: Other Measurementsmentioning
confidence: 99%
“…Jenkins et al 16 showed only a 2% higher fasting TG level in smokers than in nonsmokers among 924 men aged 50 to 59 years, in contrast to a 12% higher fasting TG level in younger smokers. Postprandial TG level was evaluated in 2 small studies: (1) Axelson et al 17 showed 50% greater TG response in habitual smokers. (2) Mero et al 18 showed that smoking raised retinyl esters and apoB-48, but not apoB-100.…”
Section: February 2001mentioning
confidence: 99%